2022
DOI: 10.1111/cns.13893
|View full text |Cite
|
Sign up to set email alerts
|

The role of Na+‐K+ATPasein the epileptic brain

Abstract: It is essential for normal structure and function of all cell membranes. Itsprimaryfunctionsincludemaintenanceiongradientacrossmembranes 2-4 anduptakeandreleaseofneurotransmitters. 5-7 Therefore, Na+-K+-ATPaseplaysacrucialroleinionhomeostasisandcellular excitability. Dysfunction of Na+-K+-ATPasemayleadtomanytypes ofcentralnervoussystem(CNS)disorders,includingepilepsy. 8-11 Epilepsyisacommonneurologicaldisordercharacterizedbyrecurrentspontaneousseizures, 12 causedbythehighlysynchronized firingofneuronswithhyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 90 publications
0
9
0
1
Order By: Relevance
“…Adequate levels of these ions are required for energy-dependent processes, such as ATP synthesis, which are essential for maintaining cellular function in the brain. 127,128 Ca 2+ ions also play an important role in the regulation of BBB permeability through its modulation of TJs and adherens junctions expression. 129,130 Circadian rhythms in ions such as Ca 2+ , K + , and Na + are also controlled by the molecular clock.…”
Section: Mg 2+mentioning
confidence: 99%
“…Adequate levels of these ions are required for energy-dependent processes, such as ATP synthesis, which are essential for maintaining cellular function in the brain. 127,128 Ca 2+ ions also play an important role in the regulation of BBB permeability through its modulation of TJs and adherens junctions expression. 129,130 Circadian rhythms in ions such as Ca 2+ , K + , and Na + are also controlled by the molecular clock.…”
Section: Mg 2+mentioning
confidence: 99%
“…115 Thus, increased expression of those transporters may be linked with neuronal dysfunction. 116,117 Furthermore, the whole-brain proteomic analysis 114 indicated a dysregulation of calcium signaling in RABV-infected cells, which was functionally confirmed by calcium-imaging tracing studied by Kim et al 10 These researchers showed that RABV differentially downregulates a range of genes related to cellular and synaptic functions by activating Ras/Erk/MAPK signaling in an M-protein-dependent manner to mediate Ca 2+ downregulation. Reduction in the calcium concentrations negatively affects neurons' spontaneous activity, which was reported during the disease kinetics.…”
Section: Ionic Dysregulationmentioning
confidence: 88%
“…54 The mechanism through which PGE2 invokes seizures is not clear but integral membrane protein Na + , K + -ATPase shows reduced activity in epilepsy. 55 In PTZadministered mice, EP1 and EP3 agonists steeply decreased the Na + , K + -ATPase activity, and EP1 and EP3 antagonists attenuated the effect of PTZ-induced decreased activity of Na + , K + -ATPase. 54 It has been found that EP1 activation during or after epilepticus causes neurodegeneration in hippocampal regions of mice and EP1-KO mice show neuroprotection against high concentrations of kainic acid.…”
Section: Pdmentioning
confidence: 90%
“…Antagonists against these two receptors alleviated epilepsy in pentylenetetrazole (PTZ)‐induced seizures in mice and agonists against these receptors ONO‐DI‐004 and ONO‐AE‐248 induced the seizures 54 . The mechanism through which PGE2 invokes seizures is not clear but integral membrane protein Na + , K + ‐ATPase shows reduced activity in epilepsy 55 . In PTZ‐administered mice, EP1 and EP3 agonists steeply decreased the Na + , K + ‐ATPase activity, and EP1 and EP3 antagonists attenuated the effect of PTZ‐induced decreased activity of Na + , K + ‐ATPase 54 .…”
Section: Epilepsymentioning
confidence: 99%